Advances in the Diagnosis and Treatment of Enthesitis-Related Arthritis - Simona Di Gennaro; Gennaro Di Matteo; Gianmarco Stornaiuolo; Federica Anselmi; Teresa Lastella; Francesca Orlando; Maria Alessio; Roberta Naddei (MDPI AG, 2023)
Enthesitis-related arthritis (ERA) represents 5-30% of all cases of juvenile idiopathic arthritis (JIA) and belongs to the spectrum of the disorders included in the group of juvenile spondyloarthritis. In the last decade, there have been considerable advances in the classification, diagnosis, monitoring, and treatment of ERA. New provisional criteria for ERA have been recently proposed by the Paediatric Rheumatology INternational Trials Organisation, as part of a wider revision of the International League of Associations for Rheumatology criteria for JIA. The increased use of magnetic resonance imaging has shown that a high proportion of patients with ERA present a subclinical axial disease. Diverse instruments can be used to assess the disease activity of ERA. The therapeutic recommendations for ERA are comparable to those applied to other non-systemic JIA categories, unless axial disease and/or enthesitis are present. In such cases, the early use of a TNF-alpha inhibitor is recommended. Novel treatment agents are promising, including IL-17/IL-23 or JAK/STAT pathways blockers.